Geographies and Cultures of International Student Experiences in Higher Education: Shared Perspectives Between Students from Different Countries - Perez-Encinas, Adriana; Rodriguez-Pomeda, Jesus (Journal of International Students, 2019)
Updated research is required on the geographies of the cultural issues that shape international students’ experiences. The growing number of students traveling to different countries implies a need to cater to cultures and values from different parts of the world. Apart from cultural and geographical aspects, there is scarce knowledge about similarities between students’ experiences abroad that takes into account their countries of origin (and, to some extent, their cultures) within those mobility flows. Using a probabilistic topic model on 59,662 international student reports from 167 countries on their mobility experiences, we examine links between the students’ experiences and their countries of origin. The results show that the geographical features of the reports are connected not only to cultural issues, but also to other factors that might affect their international experience.